The Problems of Non-Executive Court Decisions at the State Administrative Court - Ridwan Muhammad (Peneliti.net, 2020)
This research aims to (1) Know the root of the Non-Executive Administrative Court Decision Problems ( 2) To find out the legal consequences of State Administration officials who are reluctant to implement the Ambon PTUN Decision Number 10 / G / 2015 / PTUN.ABN. This studyuses a normative approach, namely research conducted by examining secondary data or library materials that are focused on examining the application of norms in positive law; and the Non Doctrinal approach, which is to synchronize the prevailing law with the empirical reality in society. This research is qualitative with a descriptive pattern. This type of research is descriptive analytical research, namely research that explains and describes what it is about the Non-Executive Judicial Verdict Problems of the State Administrative Court (Ambon State Administrative Court Decision Case Study Number: 10 / G / 2015 / PTUN. ABN By Mayor Tidore Islands) . The results show that (1) Obstacles in the execution of decisions of the State Administrative Court based on Article 116 of Law Number 51 of 2009 are: Decision, Obstacles in execution of decisions due to State Administrative Officials are Regional Heads whose position is as Political Officials, Obstacles to execution The verdict was caused by the State Administration Officer who was sued was the official who received the authority of the pseudo delegation, Obstacles regarding TUN officials' understanding of the theory of state law and AAUPB, technical obstacles, juridical obstacles (regarding laws and regulations), obstacles related to legal principles, Barriers in terms of limited authority of judges, obstacles due to changes in the regional autonomy system, obstacles due to disobedience of state administration officials. And third; Efforts that can be made against the PTUN decision that are not carried out by state administrative officials / entities such as Criminal Efforts with criminal reports and Civil Efforts by filing civil suits (2) The Role of State Administrative Courts in the practice of resolving Government Administration disputes in Indonesia due to the absence of an institution executives, as well as a strong legal basis, result in the decision of the State Administrative Court having no compulsion.